Evaluation of Serum Auto Antibodies in Multiple Sclerosis Patients: A Case Control Study - Izadi, Sadegh; Khoshniat, Saeede (International Clinical Neuroscience Journal, 2017)
Background and Purpose: Multiple sclerosis (MS) is believed to be an immune-mediated disorder that develops from an interaction of the individual’s genetic and as yet unidentified environmental causes. The prevalence of auto-antibodies in multiple sclerosis patients and their clinical associations vary in various studies. The aim of this study was to determine serum auto antibodies in multiple sclerosis patients. Methods: This cross-sectional case-control study investigated anti-phospholipids antibody (APLA), antinuclear antibody (ANA), anti-cardiolipin antibody (ACLA), anti-neutrophilic antibodies (ANCA), anti-beta-2-glycoprotein I (anti β2GPI), and anti-double strand DNA (anti-ds-DNA) in 54 consecutive patients with relapsing remitting multiple sclerosis (RRMS) and clinically isolated syndrome (CIS) who were referred to Imam Reza outpatient clinic of Shiraz University of Medical Sciences. The results were compared with 25 healthy individuals as the control group. Results: Among 54 patients with relapsing-remitting MS or clinically isolated syndrome, at least one abnormal tests were found in 15 patients (27.9%), 6 (11.1%) had positive antinuclear antibodies, 3 (5.6%) had positive anti cardiolpin antibody (ACLA) and P-ANCA was positive in 2(3.7%) of patients and C-ANCA was positive in 1(1.9%) of patients. None of the patients had any clinical manifestations other than MS symptoms. In the patient group, anti-ds-DNA antibody was positive in 5.6% of cases; statistically it had no significant difference with the control group (0%) (P=0.7), but anti- phospholipids antibody (APLA) and B2GPI were negative in all patient and control groups. The females had more positive auto-antibodies in comparison to males, but statistically their difference was not significant. Conclusion: The results of this study showed that a significant number of patients with relapsing remitting multiple sclerosis and clinically isolated syndrome have positive serum auto-antibodies tests (including ANA, ANCA and ACLA) without clinical expression of any other autoimmune disease.